2003
DOI: 10.1002/pi.1276
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties, structure and morphology of PEEK/thermotropic liquid crystalline polymer blends

Abstract: The dynamic crystallization and subsequent melting behaviour of poly(aryl ether ether ketone), PEEK, and its blends with a thermotropic liquid crystalline polymer, Vectra®, have been studied using differential scanning calorimetry, optical microscopy and wide‐angle and small‐angle X‐ray diffraction (WAXS and SAXS) techniques in a wide compositional range. Differences in crystallization rates and crystallinities were related to the structural and morphological characteristics of the blends measured by simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…Figure 4(a) shows an optical micrograph of a film prepared from a blend of the engineering thermoplastic poly(aryl ether ether ketone) (PEEK; 70% by weight) with a liquid crystal copolyester, Vectra (30% by weight). [19] which we clearly can observe by optical microscopy. 3(a), and recorded spectra with a 20 mm 20 mm at 20 mm intervals by using the conventional IR microscope with a motorized mapping stage.…”
Section: Ellis Et Al 258mentioning
confidence: 68%
“…Figure 4(a) shows an optical micrograph of a film prepared from a blend of the engineering thermoplastic poly(aryl ether ether ketone) (PEEK; 70% by weight) with a liquid crystal copolyester, Vectra (30% by weight). [19] which we clearly can observe by optical microscopy. 3(a), and recorded spectra with a 20 mm 20 mm at 20 mm intervals by using the conventional IR microscope with a motorized mapping stage.…”
Section: Ellis Et Al 258mentioning
confidence: 68%
“…This evolution of L suggests the existence of rearrangement processes and improvement (i.e. perfection and thickening) of the matrix crystals during the heating cycles subsequent to the crystallization process [11,46]. Furthermore, these recrystallization phenomena could explain the higher crystallinities obtained from DSC heating thermograms in comparison to the values derived from the cooling scans (Table 3).…”
Section: X-ray Diffraction Analysismentioning
confidence: 77%
“…Since its commercialization, PEEK has been used in a wide range of applications, from medicine to the electronics, telecommunication and transport industries (automobile, aeronautic and aerospace) [10]. Over the last decades many studies have been reported on the structural [11], mechanical [12] and thermal [13] characterization of this linear aromatic polymer, albeit only a few papers deal with such composites made of a PEEK matrix; the most relevant are those published by Shaffer et al [14], working with vapor-grown carbon nanofiber/PEEK composites, Deng et al [15], dealing with multi-walled carbon nanotube (MWCNT)/PEEK nanocomposites, and Song et al [16], who prepared sandwich like SWCNT paper/PEEK composites. Recently, our group reported the synthesis and characterization of PEEK/SWCNT composites [17].…”
Section: Introductionmentioning
confidence: 99%
“…• , which correspond to the diffraction of the (110), (111), (200) and (211) crystalline planes [39] of the orthorhombic unit cell, respectively. The appearance of peaks in WAXS patterns takes place when the material Table 3.…”
Section: Crystalline Structurementioning
confidence: 99%